Phytosanitary management of ICARDA’s germplasm seed collections for safe movement and better future use - Kumari, Safaa; Kumar, Lava; Moukahel, Abdulrahman; El Miziani, Inaam (CAB International, 2023)
Germplasm exchange from international genebanks and breeding programs is vital for successful crop improvement programs. More than 10,000 different accessions of wheat, barley, lentil, faba bean, chickpea, grasspea, and pasture and forage crops are distributed by the International Center for Agricultural Research in the Dry Areas (ICARDA) every year to around 70 countries. New accessions are added to the germplasm collections in the Center's genebank and utilized in the breeding programs. Recent years have witnessed an increasing global concern about the loss of plant genetic resources because of conflicts, human pandemic diseases, extreme weather events, pest and disease outbreaks, and natural calamities such as earthquakes, floods, etc., which led to disrupting access to germplasm and undermining social protection systems. Safety duplication of germplasm collections held in genebanks in other institutions, including international, regional, and national genebanks, as well as the Svalbard Global Seed Vault (SGSV), is one of the essential measures to safeguard germplasm and also to replenish any lost accessions and resume use and distribution of seeds to users internationally. Germplasm distribution procedures are conducted per International Plant Protection Convention phytosanitary regulations to avoid the transboundary spread of seed-borne pests and pathogens. The ICARDA’s Seed Health Laboratory exercises maximum efforts to maintain the “phytosanitary clean” health status of germplasm during regeneration, conservation, distribution and ensure compliance with phytosanitary regulations in international germplasm distributions to guarantee minimum loss of genetic resources. These efforts include the development of new methods to detect and manage seed-borne pathogens. An increase in global awareness to preserve germplasm for current and future use is crucial to combat climate challenge, malnutrition, and food insecurity.